Why Amazonian Utopias? - Colón, Marcos (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2025)
This article reimagines the Amazon through the ancestral knowledge of its Indigenous peoples, positioning the Forest as a living, biocultural system essential to planetary life. Its ethnic and linguistic diversity is inseparable from environmental integrity. The Amazonian utopias advocated here challenge extractivist capitalism by proposing alternatives grounded in Indigenous cosmologies, autonomy, and genuine sustainability. They confront the violence of land concentration, forced displacement, and ecological destruction, calling for a transformation not only in policy but in worldview. I propose a semantic reconfiguration of the concept of utopia, arguing that these visions are both ecological and epistemological, asserting that knowledge about the Amazon must emerge from within rather than be imposed from outside. Reimagining the world begins in the forest: Amazonian utopias are the future we cannot afford to ignore.